A study of a new teaching mind set: Redirecting attention away from the instructor and putting attention on the learner and the learning - uirak Kim (Halla Newcastle Education and Research Center, 2017)
Objectives Currently, many universities have been emphasizing the importance of more liberal (student-centered) education. However, there has been neither practical support nor an appropriate system for it. The purposes of this study are to show various kinds of problems arising in operating liberal education courses within the universities in Korea; to explore teaching methods utilizing e-learning in general education at university level; and to suggest corrective measures where necessary. Methods A descriptive exploratory approach underpinned this project. This involved literature searches, exploration of findings and application in the course development, testing alternative student activities, encouraging more student self-direction in studies beyond the traditional classroom and capturing the students' existing engagement with information technology. There was also a need to find a way in which an instructor, who is willing to introduce e-learning to general education, could easily utilize e-learning in their courses. In particular, considering that the features of general education are often similar or even the same in the way they are begun and maintained, I have suggested e-learning courses that many universities could utilize in collaboration with each other. Results In an effort to stimulate the communal utilization of general education among universities, not only the content producers but also content users need to cooperate each other in order to achieve quality of e-learning content and processes in general education. Conclusion Collaborative projects can encourage social interaction among students, making it easier for them to learn from one another and for those of varying skill levels to support their peers.